Influencia del tamaño de partícula y la temperatura sobre la producción de metano a partir del bagazo de fique (2011)
The aim of this work was to evaluate the effect of particle size of fique`s bagasse (FB) on anaerobic biodegradation and biogas production, by means of co-digestion of this lignocellulosic substrate using both bovine ruminal fluid and pig manure as inoculums. Anaerobic reactors were incubated by 8 days. Reducing sugar, Volatile Fatty Acid (VFA) and methane productions were measured using three different bagasse particle diameter; 5 mm (bagasse´s natural size), 2.36 mm and 0.85 mm. Reduction of bagasse particle size increased reducing sugars formation and improved substrate mass transfer to microbial inoculums. At minor particle size it was favored hydrolytic step and VFA production. Natural particle sizes of bagasse were more difficult to biodegrade than lower ones. In this sense, methane concentration was increased 19% when 0.8 mm particle size was used. Anaerobic fermentation processes were carried out at 25°C and 39°C. Methane production at 25°C, show that these microbial consortia are able to resist temperature changes and transform all products on anaerobic digestion process.